NOVEL HIGH AFFINITY INHIBITORS BASEDON THE CHEMICAL MODIFICATIONS OF 3, 4 DIHYDROXY BENZOIC ACID : DOCKING SIMULATIONS ON LIPOXYGENASE (Sciences & Technologie. C, Biotechnologies, 2007)
Modeling enzyme-inhiubitor interactions using FlexX program allowed to design novel high affinity inhibitors of soybean lipoxygenase (LOX-3). Docking results show that the binding energy of the enzyme with its inhibitor 3,4 dihydroxy benzoic acid (DHB) is ∆G = -10.564 Kj/mol. .This binding energy enhances when a hydroxyl group is added on the ring of DHB (∆G = -16.959 Kj /mol) or its carboxylic group is replaced by other functional groups, particularly a methyl hydroxyl group (∆G = - 21.127 Kj/mol). Docking study may be useful to improve the biological activity of a compound for a given target.